Can We Uncouple Neighborhood Disadvantage and Delinquent Behaviors? An Experimental Test of Family Resilience Guided by the Social Disorganization Theory of Delinquent Behaviors - Lei, Man-Kit (Fam Process, 2020)
Although the influence of neighborhood disadvantage on youth development of delinquent behavior is well established, findings from this research have yet to inform the development of family-centered prevention programming to protect youth from these erosive effects. The current paper examines the role of family integration in buffering the impact of social disadvantage in a sample of N = 298 families randomly assigned either to a control condition or to a family-based prevention program previously shown to enhance marriage and parenting. We first confirmed that neighborhood concentrated disadvantage predicted change in delinquent behaviors across the course of the study. Additionally, replicating prior work, parents participating in the Protecting Strong African American Families (ProSAAF) program, relative to those randomly assigned to the control group, significantly improved their use of effective communication strategies with each other and reduced ineffective conflict in front of youth. This resulted in a significant indirect effect of ProSAAF on change in youth delinquent behaviors. Furthermore, using mediated moderation analysis, the study tested the buffering effect of greater family integration, showing that experimentally produced change in interparental communication skills and the resulting reduction in youth exposure to parental conflict, buffered the effect of neighborhood disadvantage on change in youth delinquent behaviors, supporting a mediated moderation model in which family environments buffer neighborhood effects.